Evaluation of phenolic content and antioxidant activity in the young culm of Bambusa beecheyana munro / Mohd Izuddin Nuzul - Nuzul, Mohd Izuddin (2023)
The potential of bamboo as a source of bioactive substances and natural antioxidants for nutraceutical, pharmaceutical, and dietary sources is the subject of numerous studies today. There is a limited study on Bambusa genus, especially Bambusa beecheyana, on its phytochemical profiling and antioxidant activity. Thus, this work is a groundbreaking attempt to ascertain Bambusa beecheyana's total phenolic content, total flavonoid content, free radical scavenging activity, and phenolic identification and quantification. Using cold maceration, Soxhlet, and ultrasonic-assisted extraction procedures, the study used ethanol, methanol, and water for solvent extraction. The antioxidant properties of Bambusa beecheyana was analysed in term of total phenolic and flavonoid content and DPPH scavenging activity. In addition, extracts which have the highest content of TPC, TFC and potent DPPH value were chosen to be analysed using LCMS to identify potential compound produces in this bamboo. Moreover, the isolation of two cinnamic acid derivates were done by using semi-preparative HPLC. The content of these compounds were quantified by using HPLC-DAD. Therefore, the results from this study reveal that, Bambusa beecheyana culm extracts had an increase in the extract's dry yield (1.13-8.81%) but a constant p-coumaric acid (4) concentration (0.00035 mg/g) for all extraction methods. The bamboo culms were extracted using the ultrasonic-assisted extraction method using just 250 mL of solvent. The Soxhlet methanol culm extract contained high levels of flavonoids (43.89 ± 0.05 mg QE/g) and total phenolics (107.65 ± 0.01 mg GAE/g). When compared to ascorbic acid, the positive control, the extract had the strongest antioxidant activity, with an IC50 value of 40.43 g/mL. The Soxhlet methanol extract, the ultrasonic-assisted extract at 40 min., and the cold methanol extract were all subjected to the UHPLC-ESI-MS/MS analysis. A total of five phenolics that contained derivatives of cinnamic acid; ferulic acid, cinnamic acid, 2-hydroxybenzoic acid, p-coumaric acid and p-methoxycinnamic acid were putatively identified as a result of the investigation. The two cinnamic acid derivatives, which are p-coumaric acid (4) and p-methoxycinnamic acid (85) were used as markers to determine the content of these two compounds in all the extracts. The water extracts did not contain either compound. These findings suggested that Bambusa beecheyana extract from Soxhlet methanol might be a viable botanical source of natural antioxidants. The chemical composition database provided by this work is crucial for future commercialization on Bambusa beecheyana as a great source of functional food.